Pistia stratiotes (Jalkumbhi) - Tripathi, P.; Kumar, R.; Sharma, A. K.; Mishra, A.; Gupta, R. (Pharmacognosy Reviews)
Pistia stratiotes (Family: Araceae) is commonly used in Ayurvedic medicine. This review article is a compilation of all the updated information on its phytochemical and pharmacological activities, which were performed by different methods. Studies indicate that P. stratiotes possesses diuretic, antidiabetic, antidermatophytic, antifungal, and antimicrobial properties. These results are very encouraging and indicate that this plant should be studied more extensively to confirm the reproducibility of these results and also to reveal other potential therapeutic effects, along with some “leads” with possible isolation of active biomoieties and their mechanism of action.
Keywords: Pharmacological activities; phytochemistry; pistia stratiotes